Development and validation of a new cognitive screening test: The Hong Kong Brief Cognitive Test (HKBC). (11th April 2018) - Chiu, Helen F.K.; Zhong, Bao‐Liang; Leung, Tony; Li, S.W.; Chow, Paulina; Tsoh, Joshua; Yan, Connie; Xiang, Yu‐Tao; Wong, Mike
Abstract : Objectives: To develop and examine the validity of a new brief cognitive test with less educational bias for screening cognitive impairment. Methods: A new cognitive test, Hong Kong Brief Cognitive Test (HKBC), was developed based on review of the literature, as well as the views of an expert panel. Three groups of subjects aged 65 or above were recruited after written consent: normal older people recruited in elderly centres, people with mild NCD (neurocognitive disorder), and people with major NCD. The brief cognitive test, Mini‐Mental State Examination (MMSE) and Montreal Cognitive Assessment Scale (MoCA), were administered to the subjects. The performance of HKBC in differentiating subjects with major NCD, mild NCD, and normal older people were compared with the clinical diagnosis, as well as the MMSE and MoCA scores. Results: In total, 359 subjects were recruited, with 99 normal controls, 132 subjects with major NCD, and 128 with mild NCD. The mean MMSE, MoCA, and HKBC scores showed significant differences among the 3 groups of subjects. In the receiving operating characteristic curve analysis of the HKBC in differentiating normal subjects from those with cognitive impairment (mild NCD + major NCD), the area under the curve was 0.955 with an optimal cut‐off score of 21/22. The performances of MMSE and MoCA in differentiating normal from cognitively impaired subjects are slightly inferior to the HKBC. Conclusions: The HKBC is a brief instrument useful for screening cognitive impairment in older adults and is also useful in populations with low educational level.